WebRTC cookbook : get to grips with advanced real-time communication applications and services on WebRTC with practical, hands-on recipes /: get to grips with advanced real-time communication applications and services on WebRTC with practical, hands-on recipes. ([2015]) - Sergiienko, Andrii
No abstract available